Children's acquisition of indonesian vocabulary at an early age - Fauziah Hanum; Cut Santika; Ristawati Ristawati; Budi Febriani (Sean Institute, 2024)
This research aims to determine children's Indonesian vocabulary abilities at an early age. The aim of this research is to describe and analyze the acquisition of Indonesian in children. The subjects in this study were parents who had children under 5 years of age. In this research, no formula was used to process the data, because the method used in this research was a descriptive method with qualitative techniques. In collecting data, researchers carried out direct observations and interviews with the children's parents, going through the stages of data collection, data analysis and presenting the results of the analysis. From the data that researchers found, it can be concluded that the factors that influence language acquisition in children include: 1. age factor, this is because when children are still in the childhood stage, children will be younger to acquire language. 2. The child's first language (mother tongue), this is very influential because the first language the child acquires is the language of his mother, apart from that are environmental factors. Environmental factors are factors that play a very important role in children's language acquisition. In general, children acquire language skills through language sounds they hear from their surroundings unintentionally and without being instructed. Language skills will continue to develop step by step according to the intelligence and socio-cultural background that shapes them.